EVALUASI DATA ANTROPOMETRI ANAK-ANAK USIA 4-6 TAHUN DI JAWA TIMUR DAN APLIKASI PADA PERANCANGAN FASILITAS BELAJAR DI SEKOLAH - Herawati, Linda; Pawitra, Theresia Amelia (Jurnal Ilmiah Teknik Industri, 2013)
Anthropometry data realy important towards learning facilities design. Comfortness and functional of table an chair have correlation with physical structure of the user. Many study for 6-18 years old in anthropometry data, but for 4-6 years old children there?s no specific anthropometry data.in this research, anthropometry data for 4-6 years old child were analyze and applied to the school facilities design. 550 children from 50 schools in East Java were measured, they consist of 259 girls and 291 boys. Average weight of the boys is 21.40kg with 9.23 standard deviation; the girls average weight is 19,91kg with 5.5 standard deviation. From the body dimension gathered from this research could be applied in desigining learning facilities, such as computer table and chair. Another body dimension also used to determine seat?s width, back support?s height, etc, considering the percentile which is appropriate for each adjustment.